Enhanced thermal conductivity of carboxyl nitrile butadiene rubber composites with low-cost poly(catechol/polyamine) modified Al2O3 via biomimetic method. (February 2021) - Yang, Dan; Yu, Liyuan; Ai, Jia; Wei, Qungui; Ni, Yufeng; Zhang, Liqun
Abstract: With the miniaturization, integration, and functionalization of the electronic components, heat dissipation in the electronic devices has become a challenging issue. Owing to high polarity, carboxyl nitrile butadiene rubber (XNBR) is usually employed as a dielectric material in the electronic devices. However, low thermal conductivity of XNBR hardly satisfies the increasingly stricter demands for heat dissipation. Herein, we used low-cost poly(catechol/polyamine) (PCPA) to modify Al2 O3 nanoparticles via biomimetic method for enhancing the interfacial interaction between the Al2 O3 filler and XNBR. The ortho-polyphenols in catechol were oxidized into ortho-quinone groups in the alkaline solution. Then, the ortho-quinone groups formed a cross-linked structure to obtain PCPA via the Michael addition or Schiff base reaction with amine. The process decreased the interfacial thermal resistance and phonon scattering, resulting in an enhanced thermal conductivity. When the Al2 O3 -PCPA nanoparticles content was 30 vol%, the thermal conductivity of XNBR based composites reached up to 0.51 W/mK, which was 3.19 times that of pure XNBR (0.16 W/mK). The proposed method has potential applications in large scale production of thermally conductive composites in industries, such as electronic packaging materials and thermal management materials. Highlights: Al2 O3 -PCPA thermal conductive filler were prepared via biomimetic method. The PCPA layer decreased the interfacial thermal resistance of composites. Maximum thermal conductivity of 0.51 W/mK was obtained by XNBR composites. PCPA modification can be used for large scale production in industry.